Development and Evaluation of Interactive Learning Videos for Enhancing Arabic Speaking Skills in Junior High School - Maulana Aziz; Rudi Hartono; Masitowati Gatot (Educational Researcher Journal, 2026)
The integration of digital technologies into language education has created new opportunities to enhance students' speaking skills through interactive multimedia. However, Arabic language instruction in many junior high schools continues to rely on conventional teaching materials and non-interactive digital resources, limiting students' engagement and opportunities for independent speaking practice. This study developed and evaluated an interactive learning video designed to support Arabic speaking instruction for Grade VII students. The study employed a research and development approach using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design model. Product quality was assessed through expert validation involving specialists in Arabic language content, instructional media, and instructional design, followed by one-to-one evaluation, small-group evaluation, and field testing involving Grade VII students. Data were collected through observations, interviews, questionnaires, and product evaluation instruments and analyzed using descriptive qualitative and quantitative techniques. The developed interactive learning video achieved high levels of feasibility, receiving validation scores of 96% from the content expert, 95% from the media expert, and 91% from the instructional design expert. Classroom implementation further demonstrated high practicality and effectiveness across successive evaluation stages, indicating that iterative product refinement improved both usability and instructional performance. The findings suggest that the interactive learning video provides an engaging and pedagogically sound learning resource that facilitates Arabic speaking practice while supporting independent learning beyond classroom instruction. This study contributes to educational technology research by demonstrating how a systematic instructional design process can be translated into an accessible multimedia resource for Arabic language education and offers practical guidance for integrating interactive digital media into foreign language instruction.